Estudo da interação de nanotubos de carbono com substrato de quartzo cristalino. - Jaqueline dos Santos Soares (2011)
Single wall carbon nanotubes (SWNTs) are quasi-onedimensional structures consisting of a rolled up graphene nanoribbon. Due to their unusually large surface-to-volume ratio, SWNTs are strongly affected by the environment. Contact with a supporting substrate modifies theirproperties, and such interactions have been broadly studied as either a drawback or a solution for developing nanotube-based nanotechnologies. Researchers have for example studied the interactionof SWNTs with different substrates, and quartz becoming identified as a promising substrate for the growth of SWNTs with complex structures. Recently, combined surface- and flow-directed growth enables the controlled formation of SWNT serpentines on top of crystallinequartz. In this work we study the properties of these single wall carbon nanotubes serpentines using Raman spectroscopy. In these serpentines, we have observed the Raman spectra to obtaininformation about nanotube-quartz substrate interaction. The tube substrate interaction can be tuned and measured along the same physical nanotube, as reported here. First, we have studied the radial breathing mode (RBM) Raman spectra of single-wall carbon nanotube serpentines. The crystalline substrate strongly affects the RBM frequency and resonance energies as compared to other types of samples. Thus, we will present the Kataura plot for carbon nanotubes on the substrate. In the next step about our study of the substrate-SWNT system, we observed that the Raman spectrum depends on the tube-substrate morphology, and in some cases, it shows that the same SWNT-on-quartz system exhibits a mixture of semiconductor and metal behavior, depending on the orientation between the tube and the substrate. We also address the problem using electric force microscopy and ab initio calculations, both showing that the electronic properties along a single SWNT are being modulated via tube-substrate interaction, and corroborate our results from Raman spectroscopy. The main physical effects that have to be revealed and studied in this tube-substrate system are strain and charge transfer and how these effects vary when changing the orientation between the nanotube and the quartz surface steps. Strain depends not only on the tube-substrate interaction but also on the dynamics of the serpentine formation process, which involves a competition between the tube- surface interaction and the gas-flow-related drag forces. We also study, in this work, SWNTs under external perturbations. We employed a system that combines confocal Raman spectroscopy and nanomanipulation by atomic force microscopy probe. The G band frequency does not show significant change at the point where the tube was dragged. However, the G band frequency change increases from the drag point and, after a few microns, it abruptly returns to the same value as before the nanotube has been nanomanipulated. This result shows the presence of imperfectionsin the substrate heldind strongly the tube, creating a fixed point that prevents the spread of frequency variation. The strong substrate-nanotube interaction allows the manipulation of themorphology of single wall carbon nanotube serpentine at the specific location. This confirms the strong electronic interaction between the carbon nanotubes and the quartz substrate.